1996
DOI: 10.1159/000196556
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Lung Lavage in Pulmonary Alveolar Microlithiasis

Abstract: A case of pulmonary alveolar microlithiasis (PAM) is reported wherein total lung lavage was performed for relief of dyspnea. Characterization of the lavage material and examination of the microliths isolated from the lavage fluid confirmed previous reports of their spherical-ovoid shape and a 2:1 calcium to phosphate composition. The microliths contained considerable amounts of ionizable iron and generated oxidants in an in vitro system. A detailed biochemical analysis of the lavage fluid reflected elevations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Surfactant abnormalities have been reported for some other rare, lung diseases, such as eosinophilic granuloma [40] and pulmonary alveolar microlithiasis (table 4) [84]. Unfortunately, lavages are often performed in these rare diseases but are seldom analysed with respect to pulmonary surfactant.…”
Section: Miscellaneous Lung Diseasesmentioning
confidence: 99%
“…Surfactant abnormalities have been reported for some other rare, lung diseases, such as eosinophilic granuloma [40] and pulmonary alveolar microlithiasis (table 4) [84]. Unfortunately, lavages are often performed in these rare diseases but are seldom analysed with respect to pulmonary surfactant.…”
Section: Miscellaneous Lung Diseasesmentioning
confidence: 99%
“…Observational studies have found therapeutic BAL to be ineffective [62][63][64], except for symptomatic improvement in one case, without improvement in conventional pulmonary radiography and HRCT [36].…”
Section: Treatmentmentioning
confidence: 92%
“…Typical findings within the alveolar spaces are numerous calcified bodies, concentrically laminated with an onion skin-like appearance. The microliths usually range from 50 to 1,000 mm in diameter [22,25,[35][36][37][38][39], although microliths up to 5,000 mm in size have been reported [40]. The microliths are mainly composed of calcium and phosphorus and, to a lesser degree, of varying amounts of iron, magnesium, potassium and copper.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations